Ionic liquid based extraction of flavonoids from Elaeis guineensis leaves and their applications for gold nanoparticles synthesis - Irfan, M. (Elsevier B.V., 2017)
Gold nanoparticles (AuNPs) are attracting the researchers due to their potential applications in catalysis, bio medical, electrolysis and many other fields. However, a simple, efficient, cost effective and eco-friendly approach is still challenging to synthesize stable AuNPs. Ionic liquid (ILs) assisted bio-synthesis process can be attractive choice to produce AuNPs with enhanced colloidal stability. The aim of the study is to synthesize IL mediated stable AuNPs using bio-compounds extracted from oil palm leaves (OPL). To accelerate this study, ILC2mimBr, (1-ethyl-3-methylimidazolium bromide) was utilized for extraction of flavonoids. Changes in total flavonoids contents (TFCs) were measured over time during synthesis reaction of AuNPs to investigate its role for reduction of Au+ 3. Results suggested a decrease of TFCs from 34.83 mg CE/g to 10.98 mg CE/g during synthesis reaction which endorsed the contribution of flavonoids to reduce gold ions. The surface chemistry of AuNPs was examined through X-ray photoelectron spectroscopy (XPS) analysis which revealed a strong interaction of ILs and other organic moieties at their interfaces. AuNPs were also characterized through Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD) and Energy dispersive spectroscopy (EDAX) techniques to study the bio-functional groups, crystalline nature and presence of other elements in the reaction mixture. Colloidal AuNPs examined for two months to observe the change in the surface plasmon resonance (SPR) peak intensities, particles' size and zeta potential value characterized through UV–vis spectrophotometer, Transmission electron microscopy (TEM) and dynamic light scattering (DLS) analysis, respectively. During experimental period, SPR peaks of AuNPs remained firm to their mean position. Nevertheless, it was observed a minor difference in particles' size and zeta potential values which were changed from 13.30 nm and − 23.2 mV to 15.22 nm and − 20.9 mV respectively endorsing a stable and dispersed colloidal suspension. Based on the flavonoids, a reaction mechanism was proposed to understand the synthesis and stabilization processes of IL mediated AuNPs synthesis. © 2017 Elsevier B.V.